State-Based Conflict and Entrepreneurship: Empirical Evidence - Wim Naudé; Ernesto Amorós; Tilman Brück (Institute of Labor Economics (IZA), 2023)
This paper investigates the relationship between state-based conflict and entrepreneurship. From a survey of the existing literature, we formulate two hypotheses: (1) state-based conflict has a negative association with productive and opportunity-motivated forms of entrepreneurship, and (2) a positive association with unproductive and necessity-motivated forms of entrepreneurship. We test these hypotheses by drawing on several state-based conflict and entrepreneurship measures, using appropriate estimators, and employing robustness checks. The evidence supports our hypotheses. Necessity-motivated start-up entrepreneurship is, on average, almost three times higher in countries in conflict than in countries not in conflict. Development level matters. In countries with less unemployment, more finance, and higher levels of physical, human capital and GDP, entrepreneurship is more resilient, and the ratio of female-to-male entrepreneurs in opportunity-motivated entrepreneurship higher.
Keywords: L26; M13; J23; N40; O11; O17; 330; entrepreneurship; conflict; war; small business; employment